Prêts commerciaux à taux préférentiel - Payette, Louis (Les Cahiers de droit, 1987)
References to the "Prime Rate" or to the "Base Rate" of lending institutions are of frequent use in commercial loan agreements relating to the interest payable by the borrower. The concept of "Prime Rate" as a valid contractual arrangement has been challenged on the grounds of vagueness or on the basis that discretionary rights were given to one party, the lender ; the scope of its meaning as well as the extent of the duties of a lender lending at prime rate has been reviewed by various judicial decisions. The author reviews such decisions, Canadian, American, and French, and measures the impact of various requirements of the Civil Code, the Interest Act, the Bills of Exchange Act, the Code of Civil Procedure on agreements whereby the variable rate of interest payable by the borrower is related to "Prime Rate".